Concelho de Penedono - Itinerário(s) do Patrímónio - Luísa Alexandra Monteiro (2011)
This investigation is focused on the territory of the Portuguese municipality of Penedono, as a place of heritage and testimony of man's intervention, with the purpose of trying to understand its development potential. We try to understand this territory as part of its region, trying to understand why and how it has evolved like it did. This way, we identified its positive and negative attributes, taking in consideration the possibility of its development. Being so, we explore tourism as the most likely economic sector to help the development of Penedono and, in the range of urbanism, we designed a support structure for tourism, by creating a route of Penedono´s heritage.Firstly, this work bases itself on the recognition of Penedono's heritage, trying to assure its effective protection, valorization and publicizing it. To achieve this, we built an inventory of the material and immaterial heritage. It will be through this route that one will travel along Penedono's history, with a special focus on its points of interest, in such a way that it allows knowing the historic evolution, the different times that preceded our own and made Penedono evolve to what it is today, leaving countless structures from the past as a legacy to today's society. Along with a more theoretical approach, based upon a reflexion of the concepts attached to the heritage theme, of tourism and routes, it also arised an analysis of different references.Different ways of planning and structuring a route, in parallel with other indications that should exist around it, allowing it to become a viable project.The route presents itself as a way of promoting its users the History and heritage of Penedono, along with the possibility of combining a physical activity, the contact with nature, quality of life, as well as getting to know a way of life, in a way that it allows to understand the values and spirit of this region that lasted to our days and understanding its relevance, pointing people to its knowledge and targeting the economic, social and cultural development of Penedono´s territory, giving and recognizing value to its heritage.